Analysis of the determinant factors in university dropout: a case study of Ecuador - Núñez-Naranjo, Aracelly Fernanda (Frontiers in Education, 2024)
University dropout is a social issue that directly impacts both families and the state, characterized by disparities in enrollment and graduation based on various factors. The primary objective of this study was to analyze the determinants of university dropout supported by multifactorial analysis at a private university in Ecuador. This research was conducted within a post-positivist paradigm with a quantitative approach, utilizing digitized statistical records of students and results from a personalized survey sent to dropouts via email. Out of a total of 1,078 students admitted and/or enrolled over 5 years, a sample was analyzed from the 484 who dropped out. Student dropout is associated with personal, familial, economic, academic, and institutional factors, contributing to school abandonment with an estimated probability of 44.90%. In conclusion, a higher dropout rate was observed among male students from public institutions who did not complete the first cycle, despite having a higher number of enrollments at the university. Finally, the Multilevel Logistic Regression model can predict with 76.44% accuracy the behavior of the independent variables affecting school dropout.